(untitled) - ROSE, CHARLES G. (USA, 1990)
1.Programming NetWare / 2.Locking Services / 3.File Services / 4.Directory Services / 5.TTS / 5.Bindery Services / 6.Queue Services / 7.Print Services / 8.Connection Worstation services APIs / 9.Message Services / 10.Accounting Services / 11.Apple talk filing protocol / 12.File Server Services / 13.IPX/SPX / 14.Diagnostic services / 15.Service Advertising Protocol / 16.Value Added Process / 17.Microsoft Windows / 18.C-Worthy / 19.OOPS & C++
Incluye indice pag.929
Keywords: PROGRAMAS PARA COMPUTADOR